Efektivitas Pemanfaatan Teknologi Informasi dan Komunikasi dalam Sistem Layanan Jaringan pada Lembaga Riset Pemerintah: Studi Kualitatif di Kawasan Sains Kurnaen Sumadiharga Brin - Lalu Moh. Nazar Fajri; M. Adib Zata Ilmam; Pahrizal Iqrom; Lale Yaqutunnafis; M. Nasuhi; Abdul Hakim (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Abstract: This study aims to analyze the effectiveness of information and communication technology (ICT) utilization in network service systems at a government research institution, with a qualitative study focused on the Kurnaen Sumadiharga Science Area, BRIN. The study employed a descriptive qualitative approach using in-depth interviews, field observations, and official document analysis to explore ICT utilization practices, workflow processes, and challenges encountered during implementation. The findings indicate that ICT use has improved service workflow efficiency, facilitated internal information access, and accelerated inter-unit coordination. However, its effectiveness is not yet fully optimal due to limitations in human resource capacity, incomplete integration of service systems, and continued reliance on manual procedures in certain processes. These results suggest that ICT effectiveness is not only determined by the availability of technological infrastructure but also by organizational readiness, work culture, and effective service governance. This study emphasizes the importance of an institutional and managerial approach in assessing the role of ICT to enhance performance and service delivery in public research institutions.